Multiversities, ideas and democracy - Fallis, George, 1947- (University of Toronto Press, 2007)
Multiversities are sprawling conglomerates that provide liberal undergraduate, graduate, and professional education. As well-springs of innovation and ideas, these universities represent the core of society?s research enterprise. Multiversities, Ideas, and Democracy forcibly argues that, in the contemporary world, multiversities need to be conceptualized in a new way, that is, not just as places of teaching and research, but also as fundamental institutions of democracy.Building upon the history of universities, George Fallis discusses how the multiversity is a distinctive product of the later twentieth century and has become an institution of centrality and power. He examines five characteristics of our age ? the constrained welfare state, the information technology revolution, postmodern thought, commercialization, and globalization ? and in each case explains how the dynamic of multiversity research alters societal circumstances, leading to the alteration of the institution itself and creating challenges to its own survival. The character of our age demands reappraisal of the multiversity, Fallis argues, in order to safeguard them from so-called ?mission drift.? Writing from a multi-national perspective, this study establishes how similar ideas are shaping multiversities across the Anglo-American world.Ultimately, Multiversities, Ideas, and Democracy seeks to uncover the ethos of the multiversity and to hold such institutions accountable for their contribution to democratic life. It will appeal to anyone interested in the role of education in society.